“Assente giustificato”? L’imputato assente per «volontaria sottrazione» tra perplessità gnoseologiche e spunti sovranazionali - Bernardini, Lorenzo (Revista Ítalo-Española de Derecho Procesal, 2022)
Among the grounds that allow criminal proceedings reo absente within the Italian legal framework, that of “voluntary absconding” of the accused plays a key role. This hypothesis—laid down in Article 420a, paragraph 2 in fine, of the Code of Criminal Procedure—discloses several critical issues, both because of the lack of material factors which could infer that it has occurred in concreto, and because of the partial overlaps with the status of latitante (“fugitive”) and of irreperibile (“untraceable”) held by the suspect. Moreover, and following the ECtHR’s well-established case law on the matter, another problematic feature consists in the assessment in casu of the defendant’s actual knowledge of the proceedings, in the absence of which the Member States of the Council of Europe could be condemned—in the absence of adequate remedies—for a breach of fair trial rights (as per Article 6 ECHR) to the detriment of the person tried in absentia. Recently, the Court of Justice of the European Union has ruled upon the matter, trying to tidy up the relations between domestic laws and ECHR provisions. Applying Directive 2016/343, the Court has rebalanced the obligations incumbent on national authorities—who are obliged to carry out exhaustive and substantiated investigations—and on the accused (whose hindering conduct vis-à-vis the smooth communication of the vocatio in iudicium should be cautiously assessed). The framework thus composed, although not free of criticisms, seems to move in the direction of identifying a broader concept of ‘absconding’ within the European legal space.